Agape, eros, gender : towards a Pauline sexual ethic - Watson, Francis, 1956- (Cambridge University Press, 2000)
Issues of gender and sexuality have recently come to the fore in all humanities disciplines, and this book reflects this broad interdisciplinary situation, although its own standpoint is broadly theological. In contrast to many contemporary feminist theologies, gender and sexuality (eros) are here understood within a distinctively Christian context characterized by the reality of agape - the New Testament's term for the comprehensive divine-human love that includes the relationship of man and woman within its scope. The central problem is concern with key Pauline texts relating to gender and sexuality (1 Cor. 11, Rom. 7, Eph. 5), texts whose influence on western theology and culture has been enduring and pervasive. They are read here in conjunction with later theological and non-theological texts that reflect that influence - ranging from Augustine and Barth to Virginia Woolf, Freud and Irigaray.